Clinicoradiographic and genetic features of cerebral small vessel disease indicate variability in mode of inheritance for monoallelic HTRA1 variants. Issue 10 (12th September 2021) - Muthusamy, Karthik; Ferrer, Alejandro; Klee, Eric W.; Wierenga, Klaas J.; Gavrilova, Ralitza H.
Abstract: Background: Biallelic pathogenic variants in HTRA1 cause CARASIL. More recently, monoallelic variants have been associated with the autosomal dominant disorder CADASIL2 but not all carriers develop disease manifestations. We describe the clinicoradiologic and mutation spectrum of four new CADASIL2 individuals. Methods: Medical records at Mayo Clinic between 2013 and 2020 were retrospectively reviewed to identify patients with cerebral small vessel disease related to monoallelic HTRA1 variants. Results: Four patients met the study inclusion criteria for cerebral small vessel disease related to HTRA1 monoallelic variants. The mean age at onset of first clinical stroke was 51.25 years (range 41–64 years). The mean disease duration was 6.5 years (range 4–12). All individuals had recurrent strokes within the duration of follow‐up with a mean number of strokes per patient being 5.5 (range 2–12). Three individuals had leukoencephalopathy with brain stem involvement. Microhemorrhages were seen on brain MRI in three patients. HTRA1 monoallelic variants identified in our cohort were missense variants in three patients and a novel frameshift variation in one patient. Interestingly, two of these missense variants were previously reported in an autosomal recessive pattern of inheritance and here are associated with a dominant effect. Conclusions: Clinicoradiologic characteristics of heterozygous HTRA1 ‐related CSVD may overlap with sporadic CSVD. Heterozygous HTRA1 variants can contribute to dominant or recessive disease mechanisms. Abstract : Clinicoradiologic features of heterozygous HTRA1‐related CSVD may overlap with sporadic CVSD. The presence of vascular risk factors and a noncontributory family history should not exclude late‐onset CSVD of inherited etiology. HTRA1 variants can be disease‐causing in both heterozygous and biallelic states, but so far, there are no defining variant characteristics to determine the pattern of inheritance.